Understanding and accounting for the effects of residual stresses on cleavage fracture toughness measurements in the transition temperature regime. (April 2015) - Hurlston, R.G.; Sharples, J.K.; Sherry, A.H.
Abstract: Secondary self-balancing stresses exist in structural components due to manufacturing processes, e.g. welding. When a defect is present, such secondary stresses will influence both the local crack driving force and the level of crack-tip constraint. Fracture mechanics specimens machined from welded components can also retain significant residual stresses, and these can influence the measurement of fracture toughness. This paper describes the results of an experimental and numerical programme aimed as quantifying the effect of residual stresses on cleavage fracture toughness measured in deeply-cracked and shallow-cracked fracture mechanics specimens and with a view to correcting the resultant data. The results indicate that the influence of retained residual stresses on cleavage fracture toughness in such specimens can be characterised using two-parameter fracture mechanics. Highlights: The effect of residual stress on both crack driving force and crack-tip constraint has been examined. Current guidance can generate non-conservative cleavage fracture toughness values where residual stresses are present. The effects of residual stress on crack-tip constraint can be well characterised via two-parameter fracture mechanics. Fracture toughness data acquired using laboratory specimens containing residual stresses could be corrected.